SYNTHESIS AND PROPERTIES OF SUPERPARAMAGNETIC Y-Fe2O3 - V.O. Kotsyubynsky; V.V. Moklyak; A.B. Hrubiak (Vasyl Stefanyk Precarpathian National University, 2014)
Method of nanodispersed y-Fe2O3 synthesis by thermal decomposition of iron citrate is proposed. The investigations of obtained oxides crystalline and magnetic structures are done. Nanodispersed y-Fe2O3 with sizes of coherent scattering regions about 4-7 nm was is only one phase after gel sintering at 200, 250 and 300оС; the particles of synthesized materials are in a state of magnetic ordering and in superparamagnetic state. The influence of magnetic dipole interparticles interaction on parameters of Mossbauer spectra is observed. The phenomenological model of the differences between nanodispersed y-Fe2O3 magnetic microstructures obtained after annealing at different temperatures is presented.